Vida e obra da cordelista surda Klícia Campos : um estudo semiótico e cultural - Silva, Otávio Washington Lima (2024)
The Brazilian folk-popular poetry known as literatura de cordel - in English roughly means literature hanging on the clothesline. Moreover, the word cordel might translate as cord, string, etc. And when cited here, it will work as a shortened version for literatura de cordel. Thus, such fashion of writing is a people literary genre widely spread in the Brazilian Northeast and explored in contemporary times by diverse social groups and sectors. Currently, Portuguese is not the only language in which this genre is coined - it is possible to identify translated, adapted, and created productions in Brazilian Sign Language (the acronym in Portuguese: Libras). However, it is substantial to emphasize that this initiative is recent and has the relevant contribution of Klícia de Araújo Campos, a deaf cordelist (poet in the context of such type of literature), but from Paraíba who is also a university professor, researcher, cordelist, translator and much more. Given these considerations, this research aims to study the life and work of the deaf cordelist Klícia Campos to foster the appreciation of this genre in Brazilian Deaf Literature. Specifically, with this delving, we aim to: 1. Carry out a biographical survey of the deaf cordelist Klícia Campos; 2. Catalog the works in cordel that were created, translated, and adapted by Klícia Campos; 3. Catalog all activities carried through by the poet Klícia Campos related to the cordel in Libras; 4. Analyze the selected work based on the semiotic path of meaning proposed by Greimas, presented at the fundamental, narrative, and discursive levels; and 5. Identify the deaf cultural artifacts present in the work to be semiotically analyzed. Methodologically, this study uses a qualitative approach (Oliveira, 2014) and is exploratory (Silveira; Córdova, 2009). The data were obtained through the analysis of interviews and the collection of information on social networks and the Internet. The qualitative technique was the one used as the strategy for analyzing the data obtained. At the end of this study, it was possible to conclude that the cordelist Klícia Campos has been building a solid academic, professional, translational, and artistic career, with her primary source of inspiration being her family, which, since childhood, has influenced the poet in countless ways, contributing to her development as a people artist who is anchored in cordel and northeastern themes to bring sign art to deaf and hearing people interested in the subject. Regarding the semiotic analysis of the selected work, it was possible to verify the richness of elements present in the narrative that portray the reality of the life of the deaf person, including through the cultural artifacts present in the comic books that incorporate sign language (HQ), with Campos's life being the primary source of inspiration for the construction of the entire plot. Thus, we believe that, through this study, it was possible to strengthen the cordel in Libras as a production of Brazilian Deaf Literature, mainly by biographing the life of the first deaf cordel writer in Brazil, life being the primary source of inspiration for the construction of the entire plot. Thus, we believe that, through this study, it was possible to strengthen the cordel in Libras as a production of Brazilian Deaf Literature, mainly by biographing the life of the first deaf cordel writer in Brazil.